Overcoming Resource Nexus Conflicts With a Normative-Institutional Approach: A Case Study of Brazil - Carvalho, Priscila; Spataru, Catalina (Frontiers in Water, 2023)
Water-energy nexus research highlights the need for co-management across water and energy sectors, whereby joint planning and solutions under better integrated governance of resources could make action more efficient and cost-effective to advance the SDGs. A gap remains in the literature with regards to the normative dimension of the resource nexus. At the background of every resource nexus there are norms, which need to be considered and applied in nexus conflict resolution. Brazil has been chosen as a case study because of rising disputes connected to the fact that its electricity sector depends on hydropower plants to keep affordable tariffs, which in turn disputes water resources that serves as input to important electricity intensive sectors like WASH and also riverside communities. Hydrological factors (e.g. prolonged droughts) and non-hydrological factors (e.g. chronic delays in delivery of new plants and transmission lines) have impacted on water availability, which led to constraints for hydro power generation. Electricity prices have risen, while water quantity and quality have plunged, affecting multiple users and ecological integrity. All of which impact negatively on livelihoods and water services and sanitation, with electricity representing its fastest growing costs. The combination of qualitative research methods based on metrics, historical-institutional analysis, questionnaire, and in-depth interviews served as instruments for the assessment of the water-electricity nexus issues and development of a new legal approach to manage conflicts arising in Brazil. Most of the existing work has favoured integration of water and electricity sectors based on quantitative approach to address the interlinkages between them and tackle trade-offs. However, from a legal perspective, very little is known about how these sectors should be integrated. This study proposes a normative-institutional approach that offers a flexible, integrated, and adequate legal treatment to overcome the conflicts between water and electricity in the context of their asymmetrical governance, policies, regulation, planning and environmental injustices. Split in substantive, institutional, and procedural dimensions this approach is necessary to enhance participatory and equitable resource management based on the laws of balancing principles through fair, rational, inclusive, and transparent procedures in order to advance the SDGs in a holistic and fair manner.